2013
DOI: 10.1128/cvi.00557-12
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Vaccination among South African HIV-Exposed and Unexposed Uninfected Infants during the First 2 Years of Life

Abstract: e HIV-exposed but uninfected (HEU) infants born to HIV-infected mothers from areas in the world with a high burden of infectious disease suffer higher infectious morbidity and mortality than their HIV unexposed uninfected (HUU) peers. Vaccination provides protection from infection. The possibility exists that altered response to vaccination contributes to the higher rate of infection in HEU than in HUU infants. While short-term, cross-sectional studies support this notion, it is unclear whether or not HEU infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 29 publications
10
60
4
Order By: Relevance
“…Consistent with other studies, we observed a strong female to male predominance among the infants with pertussis [27]. Prior studies have been equivocal regarding the relationship between maternal HIV infection and pertussis [28, 29]. Here, maternal HIV appeared to modestly increase infant incidence, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with other studies, we observed a strong female to male predominance among the infants with pertussis [27]. Prior studies have been equivocal regarding the relationship between maternal HIV infection and pertussis [28, 29]. Here, maternal HIV appeared to modestly increase infant incidence, although it did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 85%
“…Maternal HIV exposure did not appear to compromise infant responses to the primary Hib vaccine series, which were robust in all subjects, consistent with previous reports (35,36). Indeed, the vaccine responses in our study are typical of observations in non-HIV-exposed populations in developing countries, where initial Hib vaccine responses may be more vigorous than in higher-income populations (37), as observed in Nepal, South Africa, and Latin America, where 95 to 100% of the infants generate protective levels of Hib-specific IgG (Ͼ1 g/ml) after a primary series.…”
Section: Discussionsupporting
confidence: 79%
“…The first, the decrease in Hib IgG concentrations from 24 to 48 weeks of age, may lead to levels below the protective threshold in the ensuing months, consistent with previous findings in both HIV-exposed and -unexposed infants (35,38,43). Such data have been invoked in support of a recommendation for a booster dose at 1 year.…”
Section: Discussionsupporting
confidence: 78%
“…The question remains as to whether or not subsequent seropositivity against pertussis or any other pathogen equates to actual protection against the disease. 24,[28][29][30] The assay that was used in this study was unable to distinguish between IgG antibodies produced as a result of primary infection or vaccination. Furthermore, while PT is exclusively secreted by B. pertussis, FHA is also secreted by B. parapertussis and B. bronchiseptica.…”
Section: Discussionmentioning
confidence: 99%